Pronunciation Errors in Speaking Committed by Non-Majoring English Students: Causes and Solution - Rizki, Julia; A. Gani, Sofyan; Marhaban, Saiful (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Errors committed by the students while studying English as a foreign language can show the students’ difficulty and be the basis of planning the proper strategy in the teaching and learning process. Therefore, this study aimed at finding out the causes of pronunciation errors in speaking skill committed by EFL learners and discovering the solutions for both students and teachers. It focused on analyzing the causes of pronunciation errors using a diagnosis proposed by Carl James. The method used in this study was a case study. Twenty non-majoring English students from International Tourism College got involved as the subject of this research. The data were collected from documentation of speaking diagnostic test results and interviewing the participants based on the test result. The findings reported that there were three causes of pronunciation errors, namely interlingual, intralingual, and communication strategy-based error. For the solution, the learners and teachers are suggested to develop the learning quality by improving the learners’ motivation to use the target language more often everywhere. Hence, this error analysis can be a reference in designing a learning strategy in teaching speaking.